1, 2‐(Bis)trifluoromethylation of Alkynes: A One‐Step Reaction to Install an Underutilized Functional Group. (11th July 2019) - Guo, Shuo; AbuSalim, Deyaa I.; Cook, Silas P.
Abstract: Modifying the electronic properties of olefins is the quintessential approach to tuning alkene reactivity. In this context, the exploration of trifluoromethyl groups as divergent electronic modifiers has not been considered. In this work, we describe a copper‐mediated 1, 2‐(bis)trifluoromethylation of acetylenes to create E ‐hexafluorobutenes ( E ‐HFBs) under blue light in a single step. The reaction proceeds with high yield and E / Z selectivity. Since the alkyne captures two trifluoromethyl groups from each molecule of bpyCu(CF3 )3, mechanistic studies were conducted to illuminate the role of the reactants. Interestingly, E ‐HFBs exhibit remarkable stability to standard olefin functionalization reactions in spite of the pendant trifluoromethyl groups. This finding has significant implications for medicine, agroscience, and materials. Abstract : Die kupfervermittelte 1, 2‐(Bis)trifluormethylierung von Acetylenen ermöglicht die Synthese von E ‐Hexafluorbutenen in einem Schritt mit hohen Ausbeuten und E / Z ‐Selektivitäten. Mechanistische Untersuchungen geben erstmalig einen Einblick in das Verhalten der Grenzorbitale des Kupferkomplexes und die Rolle von Persulfat.